The best trigonometric and bilinear approximations for functions of many variables from the classes $B^r_{p, θ}$. II - Romanyuk, A. S. (Ukrains’kyi Matematychnyi Zhurnal, 1993)
The order estimates are obtained for the best trigonometric and bilinear approximations of the classes $B^r_{p, θ}$ of functions of many variables with respect to the metric $L_q$ when $p$ and $q$ satisfy certain relations.